Nilai-Nilai Kebudayaan dalam Novel Sumirat Ing Mripat Karya Irul S. Budianto - Sabilla Eka Wahyuningsih; Sungging Widagdo; Sri Prastiti Kusuma A. (Universitas Palan, 2026)
Cultural values are life principles that guide Javanese society in acting. This article aims to analyze how Javanese cultural values are contained in the novel Sumirat Ing Mripat. The approach used is a semiotic approach from the perspective of Rolland Barthes. The analytical method used is Rolland Barthes’ semiotic theory. This analytical method consists of denotation, connotation, and myth. The analysis is carried out by linking the results of the interpretation of signs to five cultural value relationships. The semiotic approach is used to reveal the meaning and signs of Javanese cultural values. The novel Sumirat Ing Mripat was taken as a data source in this study. The results show that the novel Sumirat Ing Mripat represents cultural values. These values are the value of rationality in the relationship between humans and themselves, the value of piety in the relationship between humans and God, the value of non-rationality in the relationship between humans and others, the value of harmony in the relationship between humans and nature, and the value of deliberation in the relationship between humans and society. This study confirms that literary works function as a representation of the system of Javanese cultural values.